Identifying microscopic factors that influence ductility in disordered solids - Xiao, Hongyi; Zhang, Ge; Yang, Entao; Ivancic, Robert; Ridout, Sean; Riggleman, Robert; Durian, Douglas J.; Liu, Andrea J. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
There are empirical strategies for tuning the degree of strain localization in disordered solids, but they are system-specific and no theoretical framework explains their effectiveness or limitations. Here, we study three model disordered solids: a simulated atomic glass, an experimental granular packing, and a simulated polymer glass. We tune each system using a different strategy to exhibit two different degrees of strain localization. In tandem, we construct structuro-elastoplastic (StEP) models, which reduce descriptions of the systems to a few microscopic features that control strain localization, using a machine learning-based descriptor, softness, to represent the stability of the disordered local structure. The models are based on calculated correlations of softness and rearrangements. Without additional parameters, the models exhibit semiquantitative agreement with observed stress–strain curves and softness statistics for all systems studied. Moreover, the StEP models reveal that initial structure, the near-field effect of rearrangements on local structure, and rearrangement size, respectively, are responsible for the changes in ductility observed in the three systems. Thus, StEP models provide microscopic understanding of how strain localization depends on the interplay of structure, plasticity, and elasticity.
CRIS-Team Scopus Importer:2023-12-08
Keywords: brittle-to-ductile transition; disordered solids; machine learning; shear band